?ANTIMICROBIAL ACTIVITY OF ESSENTIAL OILS FROM SCHINUS TEREBINTHI'- FOLIUS, CYPRESS SEMPERVIRENS, CITRUS LIMON, FERULA ASSAFOETIDA. Part 1. (Biological Sciences - PJSIR, 1995)
Antibacterial activity of essential oils was studied against Escherichia coli, Shigella dysenteriae, Bacillus subtilis and Staphylococcus albus by zone inhibition method. Determination of the approximate inhibition concentrations (AIC) of the essential oils demonstrated the antimicrobial activity of each essential oils against specific microbes tested. Schinus oil was most effective against all the test bacteria. The order of effectiveness of oils was: Schinus oil> Lemon oil> Ureka Lemon oil> Cypress oil> Ferula seed oil> Ferula gum oil.